ChemInform Abstract: Straightforward Synthesis of Non‐Natural Chalcogen Peptides via Ring Opening of Aziridines. Issue 19 (18th April 2013) - Schwab, Ricardo S.; Schneider, Paulo H.
Abstract Using this method a wide range of biologically important seleno‐, telluro‐, and thiopeptides can be prepared in good to high yields.